2008
DOI: 10.1021/la702777k
|View full text |Cite
|
Sign up to set email alerts
|

Cheap and Robust Ultraflat Gold Surfaces Suitable for High-Resolution Surface Modification

Abstract: A simple procedure to elaborate robust ultraflat gold surface without clean room facilities is presented. Self-assembled 3-mercaptopropytriethoxysilane (MPTMS) on silicon was used as a buffer layer on which gold was sputtered using a common sputter-coating apparatus. The optimization of the sample position into the chamber of the sputtering machine yielded the formation of a thin (approximately 8 nm) gold layer. The characterization of the resulting gold surface (i.e., AFM, X-ray reflectivity, and diffraction)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…The FMMSs work toward reduction in the difference between γ m + γ i and γ s , by reducing γ i as a consequence of enhancement in the adhesion with metals. As presented in Table , self‐assembled silane‐based FMMSs have long been known as good adhesion promoters of Au at the surface of silicon, glass, and silica . The morphological transition to ultrasmooth, ultrathin, continuous Au films was reported in the presence of the FMMSs.…”
Section: Technical Issues In Ultrathin Metal Film Growthmentioning
confidence: 99%
“…The FMMSs work toward reduction in the difference between γ m + γ i and γ s , by reducing γ i as a consequence of enhancement in the adhesion with metals. As presented in Table , self‐assembled silane‐based FMMSs have long been known as good adhesion promoters of Au at the surface of silicon, glass, and silica . The morphological transition to ultrasmooth, ultrathin, continuous Au films was reported in the presence of the FMMSs.…”
Section: Technical Issues In Ultrathin Metal Film Growthmentioning
confidence: 99%
“…Silane‐based molecular surfactant has been shown to be an effective wetting promotor for thin Au films deposited on oxide surfaces. [ 142–147 ] Kossoy et al. have shown that continuous Au films (with a thickness down to 5.4 nm) can be deposited on fused silica substrate pretreated with (3‐mercaptopropyl)trimethoxysilane ( Figure a).…”
Section: Fabrication Of High‐quality Ultrathin Metal Filmsmentioning
confidence: 99%
“…The change of water contact angle on InN surface was observed from 3 o , indicating the O 2 plasma cleaning, to 68 o after 1.5 h reaction with MPTMS vapor, which is closed to the reported saturation contact angle (~70 o ) of MPTMS silanization [12]. The change of water contact angle on InN surface was observed from 3 o , indicating the O 2 plasma cleaning, to 68 o after 1.5 h reaction with MPTMS vapor, which is closed to the reported saturation contact angle (~70 o ) of MPTMS silanization [12].…”
Section: Surface Characterization Of Functionalized Isfetsmentioning
confidence: 48%